Unilateral visual impairment in rural south India–Andhra Pradesh Eye Disease Study (APEDS) - Srinivas Marmamula (International Journal of Ophthalmology, 2016)
AIM: To report the prevalence and causes of unilateral visual impairment (UVI) in rural population of all ages in rural Andhra Pradesh, India. METHODS: A population-based cross sectional study using a multi-stage cluster sampling methodology was carried out in West Godavari, Adilabad and Mahbubnagar districts in south India. A comprehensive eye examination that included presenting and best corrected visual acuity and dilated fundus examination was conducted by trained professionals. UVI is defined as presenting visual acuity ＜6/18 in one eye but ≥6/18 in other eye. Multiple logistic regression analysis was used to test association of UVI with socio-demographic risk factors. RESULTS: Data were analyzed for 6634/7771 participants after excluding those with bilateral visual impairment. The mean age of the participants was 27.4y (standard deviation: 17.9y), 51.9% were women and 49.1% were educated. The prevalence of UVI was 7.8% (95% CI: 7.2%-8.5%). Uncorrected refractive error (60.8%), cataract (17.4%) and retinal causes (6.6%) were the leading causes of UVI. On multiple logistic regression analyses, older age, not having education, living in well-off district had significantly higher odds of being associated with UVI. UVI was not associated with gender. CONCLUSION: UVI is common in rural south India. Most of it is due to cataract and refractive errors, both of which can be addressed at primary and secondary levels of eye care. Burden of UVI should also be considered in planning eye care services.